Impact of digital technology adoption on technological innovation in grain production - Wei Wang; Zeng Huang; Zhuoying Fu; Lu Jia; Qinghai Li; Jiahao Song (Journal of Innovation & Knowledge (JIK), 2024)
The widespread application of data technologies such as big data, artificial intelligence, and the Internet of Things plays an important role in promoting agricultural technology innovation. This article uses the 2022 survey data of farmers' economic behaviour in Hubei Province, China to construct an analytical framework and indicator system for the impact of digital technology adoption on farmers' grain production technology innovation. The relationship between digital technology adoption and farmers' grain production technology innovation is explored using binomial logistic regression models and multiple linear regression models, And use regression decomposition method to calculate the degree of impact of digital technology adoption on farmers' grain production technology innovation. The research has drawn the following conclusions: firstly, digital technology is conducive to enhancing technological innovation in grain production; The second is that innovation in grain production technology is the result of multiple factors such as digital technology, agricultural machinery and technology promotion, farmers' income, and skill training working together; The barriers and limitations of digital technology on innovation in grain production technology can be overcome by improving the service level of agricultural machinery and promoting agricultural technology training. This article believes that enhancing the innovation level of grain production technology requires attention to the adoption of digital technology and adopting diversified measures to enhance the innovation level of grain production technology amongst farmers.
Keywords: O31; O32; Q12; Q33; Q53; 650; Digital technology; Technological innovation food production; Regression decomposition